Permeability Coefficients of Murine Enterocyte Membranes for Water and Cryoprotectants - Ogurtsova, Viktoria V. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):163.